The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3892/etm.2013.1022
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging and thallium-201 scintigraphy for the diagnosis of localized pigmented villonodular synovitis arising from the elbow: A case report and review of the literature

Abstract: Pigmented villonodular synovitis (PVNS) arising from the elbow joint is extremely rare; only 24 cases have been reported. It is extremely difficult to differentiate PVNS from other soft tissue tumors on the basis of imaging findings alone. Therefore, a biopsy is required for definitive diagnosis. A 20-year-old female reported a mass on her right elbow. Physical examination revealed a tumor measuring 3.0x3.0 cm. Magnetic resonance imaging (MRI) revealed that the signal intensity of the tumor was isointense to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…1 Increased isotope accumulation (Figures 1 and 2) has been demonstrated for both pigmented villonodular synovitis (PVNS) and giant cell tumours of tendon sheaths (GCTTS) in both early and delayed phase imaging, which may mimic malignant disease. [1][2][3] Recurrent PVNS and GCTTS demonstrate similar 201 TI uptake patterns on early and delayed phase sequences. 4 It has been reported that lesions with low isotope accumulation, suggesting low metabolic activity, are highly unlikely to be PVNS or GCTTS.…”
Section: Introductionmentioning
confidence: 91%
“…1 Increased isotope accumulation (Figures 1 and 2) has been demonstrated for both pigmented villonodular synovitis (PVNS) and giant cell tumours of tendon sheaths (GCTTS) in both early and delayed phase imaging, which may mimic malignant disease. [1][2][3] Recurrent PVNS and GCTTS demonstrate similar 201 TI uptake patterns on early and delayed phase sequences. 4 It has been reported that lesions with low isotope accumulation, suggesting low metabolic activity, are highly unlikely to be PVNS or GCTTS.…”
Section: Introductionmentioning
confidence: 91%
“…Murata et al (2008) [69] were able to distinguish a chondromyxoid fibroma (benign bone tumor) from a chondrosarcoma (primary bone sarcoma) in the left knee of an 18-year-old man by using 201 Tl scintigraphy and magnetic resonance imaging. In a successive paper, the pigmented villonodular synovitis (tecnosynovial giant cell non-malignant tumor) in the right elbow of an 18-year-old woman was studied [70]. Magnetic resonance imaging revealed an isointense signal of the tumor; the use of 201 Tl scintigraphy enabled the highlighting and location of an abnormal accumulation of a cancerous mass in the elbow, which was surgically removed.…”
Section: Thallium Scintigraphymentioning
confidence: 99%
“…1,2 More commonly, this tumor is slow-growing, involving a localized portion of the joint or, in rarer cases, diffuse with malignant-type features (ie, involving the entire joint, or extra-articular lesions). [3][4][5] The incidence of intra-articular PVNS predominately occurs in Broward Health, Department of Emergency Medicine, Coral Springs, Florida Broward Health, Department of Diagnostic Radiology, Coral Springs, Florida Broward Health, Department of Internal Medicine, Coral Springs, Florida Florida Atlantic University, Boca Raton, Florida * † ‡ § young adults (median age of 30 years) and has been reported to be 1.8 per million with equal gender distribution. 4 The hip is the second most common joint affected (15% of all cases), with the knee the most prevalent of joints affected.…”
Section: Discussionmentioning
confidence: 99%